The Effect of Lecture and Small Group Discussion Method in Health Education Towards Dengue Haemorrhagic Fever Vector Larva Free Proportion in Gunungkidul Regency - Sumitro Sumitro; Hari Kusnanto J; Wahyudi Istiono (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Background:Dengue Haemorrhagic Fever is community health problem in Gunungkidul Regency, Yogyakarta. In the last five years the case and its spread have been increasing. Many efforts have been conducted to overcome case increasing, the most important is community participation in Mosquito nest eradication (PSN). Health education through radio broadcast, leaflet, dan lecture are still failing in changing community behavior to conduct PSN continuously, because the number of larva free is still low and the spread keeps increasing. Previous studies said that Small Group Discussion (SGD) was more effective in changing community behavior. Therefore, further study is needed to be done to find out the effectiveness of small group discussion (SGD) method and lecture method towards community behavior in PSN, that was measured using larva free proportion in household.Objective: The objective of the study is to find out the effect of health education using Small Group Discussion (SGD) method and lecture method towards DHF vector larva free proportion in household.Method: The study was quasi experiment with control time series design. It was conducted in Wonosari district, Karangmojo district, and Playen district in Gunungkidul Regency. The subject of the study was 412 households divided into three groups, i.e. lecture intervension group, SGD intervention group and control group. Data analysis used paired sample t-test and Mann-Whitney test.Result:There was an effect in health education using SGD method towards DHF vector larva free proportion with p-value < α (0.05). There was a difference in DHF vector larva free proportion using lecture method but it was not statistically significant, p-value > α (0.05). There were differences between SGD with lecture method and control group in increasing DHF vector larva free proportion with p-value < α (0.05).Conclusion: There was an effect in health education using SGD method and lecture method towards DHF vector larva free proportion in household. Health education using SGD method is more effective than lecture method to increase DHF vector larva free proportion in household.